IN THIS ISSUE (The Strategic Review for Southern Africa, 2021)
In presenting the results of the 'Brand South Africa' project as a special focus, this issue of the Strategic Review for Southern Africa has even more to offer than normal. The work of the guest editors is gratefully acknowledged and they will introduce the contributions to the project in more detail in the pages that follow. The journal is proud to have such a wealth of insights to share.The other articles in this volume provide additional perspectives to this special thematic focus: Albert Edgar Manyuchi looks at selected countries on the continent and critically assesses their governance of foreign direct investment. This stocktake highlights the need for careful assessments, if and when governance matters when attracting external economic interests to establish businesses and generate profit, and how best to reconcile potentially adverse interests.